Transformasi Galeri Makhga Legun Menjadi Museum Adat - Bartoven Vivit Nurdin; Dewi Ayu Hidayati; Ifaty Fadliliana Sari; Yuni Ratna Sari (Nengah Nyappur, 2022)
The construction of the Traditional Museum of the Marga Legun is still ongoing. Indigenous peoples have begun to collect historical relics and package them in the form of the Makhga Legun Gallery. The existence of this gallery shows a fairly high spirit, as well as indicating that indigenous peoples experience various obstacles in their efforts to build a traditional museum. The involvement of academics is needed to provide solutions to overcome all kinds of problems. Therefore, this community service activity was held as a form of assistance by academics. This service activity aims to facilitate indigenous peoples in the process of establishing the Legun Traditional Museum. This service activity was carried out at Lamban Balak Marga Legun, Way Urang, Kalianda. The parties involved included the local government, traditional leaders, the traditional museum manager, and the Lampung Museum manager, the resource persons. This activity was carried out on May 14, 2022. Participants were very enthusiastic about this service activity. The activity process begins with a pretest and ends with a post-test. So far, the construction of the Marga Legun's traditional museum has been very progressive. Several historical relics have been displayed in the museum's showroom. Archaeologists from the Lampung Museum assist in the identification of historical objects and provide some input so that the management of the museum is more optimal.